The impact of the blended learning system on the learning outcomes of physical education and health students: a systematic review - Muhammah Hamzah Pratama; Roesdiyanto Roesdiyanto (CV Rezki Media, 2022)
Blended learning is a learning model that is currently receiving high attention from lecturers and students in recent years. However, with so many studies addressing this issue, there has not been a systematic review that specifically analyzes all studies related to the impact of the blended learning system in physical education at the tertiary level. Thus, this study aims to evaluate the overall effect of blended learning in physical education at the university level. Search literature studies obtained using Google Scholar, PubMed, Eric and Science Direct databases. In searching the literature, researchers used the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines. The literature search strategy includes the following predefined keyword combinations: “blended learning” AND “physical education” AND “sports” AND “college students”. All studies were extracted from the database and data analysis was carried out using the Mendeley application to filter out articles that were duplicates or did not match the research studies. Of the 665 publications obtained from the Google Scholar database, DOAJ, Eric and Science Direct, after passing through the screening, only 13 articles were found that matched the research intervention. The conclusion from the data analysis that has been done explains that the blended learning model is very good at improving students' motor skills. Subsequent significant improvements can also be found at the understanding or cognitive level of students using the blended learning method. In addition, volleyball is one of the most researched and studied sports in all sports, such as badminton, dance, football, athletics, and martial arts. Therefore, further research is expected to be able to dig deeper into the impact of blended learning on increasing student attitude scores and optimizing the use of blended in athletics or martial arts.